Numerical Study of the Effect of Out-of-Plane Distance in the Lateral Direction at the Mid-Span of a Steel Beam on the Sectional Moment Capacity - Ahmed Mohamed Sayed; Nageh M. Ali; Mishal H. Aljarbou; Abdullah Alzlfawi; Salman Aldhobaib; Hani Alanazi; Abdulmalik H. Altuwayjiri (Buildings)
Steel I-beams may be subject to deviation from their normal path towards the lateral direction due to obstacles along their axis line. This deviation in the lateral direction, i.e., the out-of-plane distance, affects the behavior of the steel beams and may reduce their ultimate capacity. To obtain this effect, finite element modeling (FEM) was used to model these beams with and without an out-of-plane distance at the mid-span beam length with several different variables. These variables were the out-of-plane distance, cross-section dimensions, beam length, and steel yield stress. The reliability of using FEM simulation was confirmed by comparing the experimental test results of 25 available steel beams in previous studies. The results indicate the high accuracy of the simulation of this beam in terms of ultimate capacity, structural behavior, and deformation patterns. After verifying the results, 116 broad-flange I-beam (BFIB) steel beams with different out-of-plane distances were modeled. The results showed that using an out-of-plane distance equal to the flange width of the BFIB-300 cross-section caused a 60% decrease in the ultimate capacity. The reduction ratios in the ultimate moment capacity in out-of-plane steel beams were directly proportional to the out-of-plane distance, cross-sectional dimensions, and steel yield stress, while the beam length had no effect. Failure in beams containing an out-of-plane distance occurs as a result of a global buckling in the upper flange, which contains tensile stresses at the outer edge and compressive stresses at the inner edge, with stress concentration occurring at the point of contact of the out-of-plane part with the main beam. The prediction results of the design codes were compared with the results of experimental tests and the FEM analysis of the beams with and without out-of-plane distances. For all the beams with out-of-plane distances, all the design codes were unable to predict this ultimate capacity.